1998
DOI: 10.1037/0022-006x.66.5.832
|View full text |Cite
|
Sign up to set email alerts
|

Superior efficacy of cognitive-behavioral therapy for urban crack cocaine abusers: Main and matching effects.

Abstract: This study evaluated the efficacy of cognitive-behavioral therapy (CBT) and 12-step facilitation (12SF) in treating cocaine abuse. Participants (N = 128) were randomly assigned to treatment conditions and assessed at baseline and at Weeks 4, 8, 12, and 26. Treatment lasted for 12 weeks. It was hypothesized that participants treated with CBT would be significantly more likely to achieve abstinence from cocaine than participants treated with 12SF. A series of patient-treatment matching hypotheses was also propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 31 publications
1
113
0
1
Order By: Relevance
“…Meta-analyses and extensive reviews of the literature have established that cognitive behavior approaches have strong empirical support for use in treatment of alcohol use disorders (44,45) and several non-substance-related psychiatric disorders (46) and that these approaches have been demonstrated to be effective in drug-using populations as well (47). Several research groups have demonstrated the efficacy of cognitive behavior therapy in the treatment of cocaine-dependent outpatients, particularly depressed and more severely dependent cocaine users (48)(49)(50)(51)(52)(53)(54), and have shown that cognitive behavior therapy is compatible and possibly has additive effects when combined with pharmacotherapies such as disulfiram (55,56). Furthermore, cognitive behavior therapy is characterized by an emphasis on the development of skills that can be used initially to foster abstinence but can also be applied to a range of co-occurring problems.…”
Section: Cognitive Behavior and Skills Training Therapiesmentioning
confidence: 99%
“…Meta-analyses and extensive reviews of the literature have established that cognitive behavior approaches have strong empirical support for use in treatment of alcohol use disorders (44,45) and several non-substance-related psychiatric disorders (46) and that these approaches have been demonstrated to be effective in drug-using populations as well (47). Several research groups have demonstrated the efficacy of cognitive behavior therapy in the treatment of cocaine-dependent outpatients, particularly depressed and more severely dependent cocaine users (48)(49)(50)(51)(52)(53)(54), and have shown that cognitive behavior therapy is compatible and possibly has additive effects when combined with pharmacotherapies such as disulfiram (55,56). Furthermore, cognitive behavior therapy is characterized by an emphasis on the development of skills that can be used initially to foster abstinence but can also be applied to a range of co-occurring problems.…”
Section: Cognitive Behavior and Skills Training Therapiesmentioning
confidence: 99%
“…Support for CBT in the treatment of cocaine dependence has been demonstrated (Carroll et al, 1991(Carroll et al, , 1994Maude-Griffin et al, 1998;McKay et al, 1997;Rohsenow et al, 2000;Schmitz et al, 1997), with recent evidence suggesting additive effects when combining CBT with pharmacotherapy (Carroll et al, 2004a;Carroll et al, 1998;Schmitz et al, 2001). CBT is considered to be more powerful than ClinMan, but not sufficiently potent to override medication effects (Carroll et al, 2004b).…”
Section: Behavioral Platformsmentioning
confidence: 99%
“…Relapseprevention cognitive behavioural therapy (RP-CBT) is derived from a cognitive model of drug misuse. The emphasis is on identifying and modifying irrational thoughts, managing negative mood and intervening after a lapse to prevent a full-blown relapse [26]. The emphasis is on development of skills to (a) recognize High Risk Situations (HRS) or states where clients are most vulnerable to drug use, (b) avoidance of HRS, and (C) to use a variety of cognitive and behavioural strategies to cope effectively with these situations.…”
Section: Course Of Treatment and Assessment Of Progressmentioning
confidence: 99%
“…The emphasis is on development of skills to (a) recognize High Risk Situations (HRS) or states where clients are most vulnerable to drug use, (b) avoidance of HRS, and (C) to use a variety of cognitive and behavioural strategies to cope effectively with these situations. RP-CBT differs from typical CBT in that the accent is on training people who misuse drugs to develop skills to identify and anticipate situations or states where they are most vulnerable to drug use and to use a range of cognitive and behavioural strategies to cope effectively with these situations [26].…”
Section: Course Of Treatment and Assessment Of Progressmentioning
confidence: 99%